2023
DOI: 10.1038/s41598-023-38912-1
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal X-ray spectroscopy investigation of uranium speciation in ThTi2O6 compounds with the brannerite structure

Malin C. Dixon Wilkins,
Luke T. Townsend,
Martin C. Stennett
et al.

Abstract: ThTi2O6 derived compounds with the brannerite structure were designed, synthesised, and characterised with the aim of stabilising incorporation of U5+ or U6+, at dilute concentration. Appropriate charge compensation was targeted by co-substitution of Gd3+, Ca2+, Al3+, or Cr3+, on the Th or Ti site. U L3 edge X-ray Absorption Near Edge Spectroscopy (XANES) and High Energy Resolution Fluorescence Detected U M4 edge XANES evidenced U5+ as the major oxidation state in all compounds, with a minor fraction of U6+ (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In this collection, Corkhill et al 2 investigated titanate ceramics with the pyrochlore structure using photoemission and X-ray absorption spectroscopy (XAS) and showed the possibility of chemical flexibility in terms of crystal-chemical design principles of pyrochlore structure. Additionally, Corkhill et al 3 explored the mineral brannerite UTi 2 O 6 as a possible host phase for the immobilization of long-lived actinides, such as plutonium. Their investigation demonstrated that the ThTi 2 O 6 brannerite structure can incorporate a small fraction of U 6+ alongside a more significant inventory of U 5+ , achieved through charge compensation on the Th or Ti site.…”
mentioning
confidence: 99%
“…In this collection, Corkhill et al 2 investigated titanate ceramics with the pyrochlore structure using photoemission and X-ray absorption spectroscopy (XAS) and showed the possibility of chemical flexibility in terms of crystal-chemical design principles of pyrochlore structure. Additionally, Corkhill et al 3 explored the mineral brannerite UTi 2 O 6 as a possible host phase for the immobilization of long-lived actinides, such as plutonium. Their investigation demonstrated that the ThTi 2 O 6 brannerite structure can incorporate a small fraction of U 6+ alongside a more significant inventory of U 5+ , achieved through charge compensation on the Th or Ti site.…”
mentioning
confidence: 99%